Transnational corporations as entities of informal influence. Some reflections based on the example of their engagement in activities directed at LGBT groups in Poland - Bielska, Beata; Tamborska, Katarzyna (Annales. Etyka w Życiu Gospodarczym, 2019)
The paper explores the assertion about multi-faceted tools of impact used by large corporations that aim to limit the subjectivity of consumers. It is based on the concept of “deep capture” (Hanson & Yosifon, 2003). Deep capture suggests that the consumers have only the idea of their own subjectivity, and that human behaviour is largely dependent on external situational factors rather than the individuals’ dispositions. In this context, the present authors analyse the role of large corporations in shaping the image of LGBT people in Poland. Noteworthy is the consideration to build and strengthen the belief that LGBT people are a group which suffers discrimination, to which anyone should make gestures of support throughout consumer decisions. An overview of the actions of business entities for LGBT groups in Poland allows us state that these actions cannot be called large-scale. The actions of Polish companies can be recognised as not very intense or committed. Western transnational corporations have vast experience in actions for LGBT people, but this is not necessarily the case in Poland.